Implementasi Pemeriksaan Kesehatan Gratis Melalui Bakti Sosial di Swarangan - Wulan Pratiwi; Putri Nur Riani; Muhammad Ilham Farihi; Ratih Indah Sari; Yuvita Yuvita (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2026)
Non-Communicable Diseases (NCDs) represent a major and increasing public health challenge in Tanah Laut Regency, particularly in Swarangan Village. The most commonly identified NCDs in the community include diabetes mellitus, gout, cardiovascular disease, and stroke. This community service program aimed to increase community awareness of NCD prevention and facilitate early detection through free health screening services. The program was implemented through collaboration between Borneo Citra Medika Polytechnic of Health and Borneo Citra Medika Hospital, involving healthcare professionals and academic staff. A total of 150 community members participated in the activity. The intervention began with a medical anamnesis to identify health complaints and risk factors, followed by targeted laboratory examinations for participants with clinical indications. The screening results showed that 35 participants (23.3%) underwent blood glucose testing, 29 participants (19.3%) underwent uric acid testing, and 44 participants (29.3%) underwent cholesterol testing, indicating a considerable proportion of individuals at risk of NCDs. The program contributed to increased community awareness, early identification of risk factors, and strengthened preventive health efforts at the community level.